Analysis of the results of management and regulation indicators after privatization: case study of Light Electricity Services (Revista de Administração, 2014)
Privatization is one of the most used public manegement tools in the late 20th century. However, the understanding and the discussion of its results are not consolidated, creating a significant gap in research. Thus, in this study, we aimed at analyzing the results of the privatization of Light Serviços de Eletricidade S.A., after its implementation. Methodologically, we focused on two dimensions: firstly, we evaluated the organization's performance from the point of view of consumers, and, secondly, we assessed the extent to which the performance of the regulatory agency has begun to influence the management performance of Light after privatization. Therefore, we investigated data on the variation of gross revenue, the evolution of net income and investment, the DEC and FEC indicators, which measure, respectively, duration and frequency of interruptions in electricity supply of Light, besides the average price per megawatt-hour, the amount of complaints and the variation in the number of consumers. Based on the results, we can infer that new investments enhance firm's performance and reduce complaints. In addition, there was no evidence that privatization has contributed to the improvement of technical indicators of Light.